Transformation and products of captopril with humic constituents during laccase-catalyzed oxidation: Role of reactive intermediates. (1st December 2016) - Du, Penghui; Zhao, He; Liu, Chenming; Huang, Qingguo; Cao, Hongbin
Abstract: The transformation of captopril (CAP), a widely-used thiol drug, was studied with the presence of dissolved model humic constituents (HCs) in a laccase-catalyzed system. Reaction products were analyzed by ultra-performance liquid chromatography coupled to time-of-flight mass spectrometry and condensed fukui function computation. CAP reacted with different model HCs in the enzymatic system for 1 h, ranging from 75% (syringic acid) to 96% ( p -coumaric acid). In the absence of HCs, only 15% of CAP was removed through self-coupling. The presence of HCs apparently changed the transformation of CAP in aqueous environment, and the HC reactive intermediates played an important role. First, during laccase catalysis, HCs with different structures were oxidized to produce reactive intermediates, including phenoxyl radical cation, ortho -, and para -quinone intermediates. Second, these intermediates were readily attacked by CAP via nucleophilic reactions, forming C–S–C covalent conjugates. More importantly, the standard reduction potential of these intermediates is a critical parameter, as PCA showed the highest reactivity to the nucleophilic addition reaction with CAP by forming phenoxy radical cations. While SYR showed the least reactivity due to the formation of para -quinone intermediates. Therefore, the functional groups on HCs could greatly influence the cross-coupling with CAP, as well as the type and stability of the coupling products. This work clearly demonstrated the transformation of CAP and other thiol drugs with the presence of HCs in aqueous environment, which is similar to the natural humification process. Graphical abstract: Highlights: The presence of HCs promotes CAP transformation in laccase-catalyzed system. Different HC leads to different reactive intermediate, reaction rate, and pathway. HC reactive intermediates play important role in CAP transformation. A theoretical model is used for reaction sites prediction.